SULFUR AND CARBON ISOTOPE RECORDS FROM 1700 TO 800 MA CARBONATES OF THE JIXIAN SECTION, NORTHERN CHINA: IMPLICATIONS FOR SECULAR ISOTOPE VARIATIONS IN PROTEROZOIC SEAWATER AND RELATIONSHIPS TO GLOBAL SUPERCONTINENTAL EVENTS - Chu X.; Zhang T.; Zhang Q.; Lyons T.W. (My University, 2007)
This study is a comprehensive, stable isotope survey of the marine carbonate-dominated, upper Paleo- to lower Neoproterozoic stratigraphy of Jixian County, China. Carbonate-associated sulfate (CAS) was extracted and measured for δ³⁴SCAS using the same samples analyzed for δ¹³Ccarbonate. This integrated proxy approach is a step towards a more comprehensive picture of secular variation in the composition of Proterozoic seawater. We specifically sampled marine carbonate intervals from the lower section of the Chuanlinggou Formation, Changcheng Group (ca. 1700 Ma) to the top of the Jingeryu Formation, Qingbaikou Group (ca. 800 Ma). δ¹³Ccarbonate values are mostly negative in the upper Paleoproterozoic Changcheng Group, with an ascending trend from −3‰ to 0‰. We observed variation of approximately 0 ± 1‰ in the Mesoproterozoic Jixian Group, and positive values of +2 ± 2‰ characterize the lower Neoproterozoic Qingbaikou Group. Stratigraphic variations in δ³⁴SCAS are more remarkable in their ranges and magnitudes, including conspicuously high values exceeding +30‰ in the three intervals at ca. 1700 Ma, 1300–1100 Ma, and 1000–900 Ma. In the Changcheng Group, δ³⁴SCAS values are typically higher than +25‰, with only a few values of less than +15‰. In contrast, most of the data spanning from the Mesoproterozoic Tieling Formation of the Jixian Group to the lower Neoproterozoic Jingeryu Formation of the Qingbaikou Group are highly variable between +10‰ and +25‰, with some values exceeding +25‰.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой